An Easy Access to Organic Salt‐Based Stimuli‐Responsive and Multifunctional Supramolecular Hydrogels. Issue 27 (3rd June 2016) - Majumder, Joydeb; Dastidar, Parthasarathi
Abstract: By exploiting orthogonal hydrogen bonding involving supramolecular synthons and hydrophobic/hydrophilic interactions, a new series of simple organic salt based hydrogelators derived from pyrene butyric acid and its β‐alanine amide derivative, and various primary amines has been achieved. The hydrogels were characterised by microscopy, table‐top rheology and dynamic rheology. FTIR, variable‐temperature 1 H NMR and emission spectroscopy established the role of various supramolecular interactions such as hydrogen bonding and π–π stacking in hydrogelation. Single‐crystal X‐ray diffraction (SXRD) studies supported the conclusion that orthogonal hydrogen bonding involving amide–amide and primary ammonium monocarboxylate (PAM) synthons indeed played a crucial role in hydrogelation. The hydrogels were found to be stimuli‐responsive and were capable of sensing ammonia and adsorbing water‐soluble dye (methylene blue). All the hydrogelators were biocompatible (MTT assay in RAW 264.7 cells), indicating their suitability for use in drug delivery. Abstract : Functional hydrogels : A judicious combination of supramolecular synthons and hydrophobic/hydrophilic interactions has been employed in the design of stimuli‐responsive functional organic salt‐based supramolecular hydrogels that are capable of showing ammonia‐sensing and dye‐adsorbing properties (see figure).